Asymmetric Buckling of the Annular Plate with an Internal Source of Heat - Pham, Tan Hung (Journal of Technical Education Science, 2022)
In this article, the axisymmetric stability of an elastic annular plate with distributed internal heat source under uniform constant compressive radial loading at the outer edge is investigated. The governing and compatibility equations of the annular plate are taken from modified Karman’s equations, which are solved by the shooting method. The effect of the density of distributed internal heat source on critical load is investigated and discussed in detail. The numerical results of the plate without an internal heat source are in good agreement with the results from the literature, validating the effectiveness and advantages of the current method. The critical buckling load increases with a rise of the density of distributed internal heat sources. Moreover, an increase of wave number increases the critical buckling loads of the plate. The results of this research can be considered as benchmark solutions for buckling of the annular plates with an internal heat source.